2017
DOI: 10.1002/ente.201700393
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Polymer Solar Cells Spray‐Coated from Non‐Halogenated Solvents towards Practical Fabrication

Abstract: In the past decade, the power conversion efficiencies (PCEs) of polymer solar cells (PSCs) have been improved significantly. However, most efficient PSCs are based on halogenated solvents and the spin‐coating technique. To meet the requirements of practical fabrication, PSCs processed from non‐halogenated solvents using scalable deposition techniques are required. In this work, a non‐halogenated solvent system, o‐xylene/benzyl phenyl ether (BPE), was utilized to fabricate PSCs. The PSC obtained through spin co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…However, the spin-coating method is not suitable for large-scale solar panel manufacture because: (i) the rotation of large substrates for mass production is not feasible, (ii) the discontinuous coating process leads to low throughput, and (iii) most of the active materials and solvents are wasted during the active layer deposition. Therefore, several scalable deposition methods (Figure a), such as blade coating, ,,,,,,,,, slot-die coating, spray coating, and inkjet printing, , have been developed and applied in various eco-friendly PSC studies. However, devices fabricated using these coating methods are generally unable to achieve the performances of spin-coated devices under the same optimized conditions because of the different film formation mechanisms.…”
Section: Challenges and Outlook Of Eco-friendly Pscsmentioning
confidence: 99%
“…However, the spin-coating method is not suitable for large-scale solar panel manufacture because: (i) the rotation of large substrates for mass production is not feasible, (ii) the discontinuous coating process leads to low throughput, and (iii) most of the active materials and solvents are wasted during the active layer deposition. Therefore, several scalable deposition methods (Figure a), such as blade coating, ,,,,,,,,, slot-die coating, spray coating, and inkjet printing, , have been developed and applied in various eco-friendly PSC studies. However, devices fabricated using these coating methods are generally unable to achieve the performances of spin-coated devices under the same optimized conditions because of the different film formation mechanisms.…”
Section: Challenges and Outlook Of Eco-friendly Pscsmentioning
confidence: 99%
“…The highest μ e and μ h values with the most balanced μ e /μ h ratio for SVA-assisted one-step spraying fullerene- and nonfullerene-based devices make them exhibit the best device performance among all of the corresponding spraying OSCs (Figure ). The PCEs of conventional two-step spraying fullerene- and nonfullerene-based OSCs in previous reports are shown in Figure S14. ,,,,,, It can be found that the SVA-assisted one-step spraying technique is proposed for the first time and the obtained PCEs are comparable to those of the two-step spraying OSCs reported to date because of better PFN self-assembly, finer donor–acceptor phase separation, and smoother film morphology.…”
Section: Results and Discussionmentioning
confidence: 61%
“…Organic solar cells (OSCs) have been widely studied in recent years due to their many advantages including low cost, flexibility, and environmentally-friendly solution processability. So far, the power conversion efficiency (PCE) of OSCs has pulled into 18% with the help of abounding efforts in both the ingenious material design and reasonable device optimization, exhibiting a promising prospect toward industrialization and commercialization. However, the records of high-performance OSCs were generally achieved by a lab-scale spin-coating method, which is not compatible with large-scale manufacturing of solar modules in view of high material cost and limited device area . Therefore, different printing technologies, such as spray coating, slot die, and doctor blading, , were extensively studied for future OSC production. , Among these techniques, spray coating possesses great potential for manufacturing because of its unique and fascinating advantages like compatibility for various types of substrates, less demanding requirements for solute solubility and solution rheological behavior, and improved photon absorption by textured surface morphology, attracting more and more attention from both academia and industry …”
Section: Introductionmentioning
confidence: 99%
“…[ 532,533 ] Coupled with optical curing (where halide perovskite was exposed to high‐density infrared light at a short period of time), fPSCs with PCE of 8.1% were realized via spray coating. [ 534,535 ] Thus far, spray coating is widely studied to prepare polymer solar cells, [ 536,537 ] but its involvement in PSCs is still lacking. Considering the successful application of spray coating in polymer solar cells, the situation for PSCs could be similar.…”
Section: Scalability: Module Productionmentioning
confidence: 99%